Progress in Research on Metal Ion Crosslinking Alginate-Based Gels - Yantao Wang; Zhenpeng Shen; Huili Wang; Zhaoping Song; Dehai Yu; Guodong Li; Xiaona Liu; Wenxia Liu (Gels)
Alginate is an important natural biopolymer and metal ion-induced gelation is one of its most significant functional properties. Alginate-based hydrogels crosslinked with metal ions are commonly utilized in the food, biomedical, tissue engineering, and environment fields. The process of metal ion-induced alginate gelation has been the subject of thorough research over the last few decades. This review aims to summarize the mechanisms of alginate hydrogels induced by different cations (primarily including Ca2+, Ba2+, Cu2+, Sr2+, Fe2+/Fe3+, and Al3+). Metal ion-induced alginate gelation shows different preferences for α-L-guluronic acid (G), β-D-mannuronic acid (M), and GM blocks. Some metal ions can also selectively bind to the carboxyl groups of guluronic acid. The properties and applications of these alginate-based hydrogels are also discussed. The primary objective of this review is to provide useful information for exploring the practical applications of alginate.